Hope, Social Support, Trust, and Significancy of Job Security in Improving Well-Being - Chie, Ho Hwi (ANIMA Indonesian Psychological Journal, 2010)
The aim of this study was to verify that job security has indirect influence on well-being by means of hope, social support and trust. Two hundred and eighteen responders, who were working either at an oil company or in an automotive company based in Jakarta, were selected to test this hypothetical model. Purposive Sampling technique was used to compile the data needed, which were recorded as scales of wellbeing, hope, social support, trust, and job security. Structural Equation Model was used to analyze the data. The results showed that the hypothetic model was fit, where job security could not influence wellbeing directly. Having hope, social support and trust, however, could enable those who have high rank of job security, to reach their well-being. Further studies are needed for wider- ranging applications of this new model. Innovative technique developments are still recommended to overcome this new model’s constraints. Penelitian ini bertujuan untuk membuktikan hipotesis, bahwa job security berpengaruh tidak langsung terhadap well-being, melalui hope, social support, dan trust. Sebanyak 218 responden, yaitu karyawan yang bekerja pada perusahaan minyak internasional ataupun perusahaan otomotif di Jakarta, telah dipilih untuk menguji model hipotesis. Teknik sampling yang digunakan adalah pur- posive sampling, dengan skala well-being, hope, social support, trust, dan job security. Analisa data dilakukan melalui Structural Equation Model. Hasil penelitian menunjukkan, bahwa job security berpengaruh tidak langsung terhadap well-being. Adanya hope, social support, dan trust, memung- kinkan individu yang memiliki job security yang tinggi, mencapai well-being. Penelitian lebih lanjut masih perlu dilakukan untuk generalisasi model hipotesis ini, termasuk menggunakan teknik-teknik yang menjadi keterbatasan penelitian ini.